2013
DOI: 10.4103/0189-6725.125446
|View full text |Cite
|
Sign up to set email alerts
|

Childhood unintentional injuries: Supervision and first aid provided

Abstract: Especially young children are at risk for unintentional injuries. Lack of appropriate supervision increases this risk. Prevention education of parents and children may help to protect children from injuries. First-aid training should also be more accessible to civilians as both the providing of as well as the quality of first-aid provided lacked in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Similar alternative therapies have been reported as common practice after a burn injury in other African countries like South Africa and Nigeria. 8 , 9 The other alternative therapies which were reported from South Africa and Nigeria but not common in caregivers in our study were pap, chalk, cow dung and salt. It was also noted that even in some European countries like Turkey and the United Kingdom, inappropriate methods were popular after a burn injury and these included yoghurt, toothpaste, tomato paste, ice, chalk, raw egg whites, or sliced potato.…”
Section: Discussionmentioning
confidence: 57%
“…Similar alternative therapies have been reported as common practice after a burn injury in other African countries like South Africa and Nigeria. 8 , 9 The other alternative therapies which were reported from South Africa and Nigeria but not common in caregivers in our study were pap, chalk, cow dung and salt. It was also noted that even in some European countries like Turkey and the United Kingdom, inappropriate methods were popular after a burn injury and these included yoghurt, toothpaste, tomato paste, ice, chalk, raw egg whites, or sliced potato.…”
Section: Discussionmentioning
confidence: 57%
“…A systematic review of first aid provided by lay people on trauma victims found that incorrect first aid was provided to 83.7% of cases [ 23 ]. Similarly, descriptive studies for common unintentional injuries such as burns, cuts, falls, suffocation among children in Turkey, South Africa, Ghana and Saudi-Arabia revealed that majority of the subjects had been treated with inappropriate interventions such as kitchen ingredients (yogurt, raw egg whites, honey, tomato paste) and household materials (toothpaste, aloe vera, Lavender oil) [ 39 , 40 , 41 , 42 ]. Although our study did not assess the appropriateness of the first aid, the negative findings associated with untrained providers raises questions on whether they provided appropriate first aid or not.…”
Section: Discussionmentioning
confidence: 99%
“…A alta prevalência de queimaduras em MMSS estiveram em 65,3%, seguida de 58,9% no tronco, são registradas em várias abordagens sobre a temática (7,(14)(15) . Podese relacionar a queimadura em membros superiores com a posição da criança na hora do acidente, uma vez que puxam para si objetos contendo líquidos aquecidos como panelas (16) .…”
Section: Variáveisunclassified